Statistical Optimization for Biobutanol Production by Clostridium acetobutylicum ATCC 824 from Oil Palm Frond (OPF) Juice Using Response Surface Methodology - Nur Syazana, Muhamad Nasrah; Mior Ahmad Khushairi, Mohd Zahari; N., Masngut; Hidayah, Ariffin (EDP Sciences, 2017)

(untitled)
The interaction between incubation temperature, yeast extract concentration and inoculum size was investigated to optimize critical environmental parameters for production of biobutanol from oil palm frond (OPF) juice by Clostridium acetobutylicum ATCC 824 using response surface methodology (RSM). A central composite design (CCD) was applied as the experimental design and a polynomial regression model with quadratic term was used to analyse the experimental data using analysis of variance (ANOVA). ANOVA analysis showed that the model was very significant (p < 0.0001) for the biobutanol production. The incubation temperature, yeast extract concentration and inoculum size showed significant value at p < 0.005. The results of optimization process showed that a maximum biobutanol production was obtained under the condition of temperature 37 °C, yeast extract concentration 5.5 g/L and inoculum size 10%. Under these optimized conditions, the highest biobutanol yield was 0.3054 g/g after 144 hours of incubation period. The model was validated by applying the optimized conditions and 0.2992 g/g biobutanol yield was obtained. These experimental findings were in close agreement with the model prediction, with a difference of only 9.76%.